Oxetane cis- and trans beta-amino-acid scaffolds from D-xylose by efficient S(N)2 reactions in oxetane rings: methyl and hydroxymethyl analogues of the antibiotic oxetin, an oxetane beta-amino-acid - Jenkinson, S; Harris, T; Fleet, G (2004)
Highly regioselective reactions of a benzylidene-protected oxetane with (i) triethylsilane-trifluoroacetic acid and (ii) Hanessian-Hullar bromination provide efficient access to 3-hydroxyoxetane carboxylates in which only the C-3 OH is unprotected. Subsequent nucleophilic displacements of the corresponding triflates by azide proceeds in consistently excellent yields without any elimination to provide syntheses of scaffolds for a range of methyl and hydroxymethyl analogues of the antibiotic oxetin, a naturally occurring oxetane cis-β-amino acid. © 2004 Elsevier Ltd. All rights reserved.